Generación de energía eléctrica a través del biogás para la avícola de la universidad técnica de Cotopaxi campus Salache - Tonato Sangucho, Jessica Janeth (2019)
The purpose of this thesis project is the study of new energy sources that allow us a generation more clean and friendly to the environment, this area can consider the use of biogas obtained from the residual biomass moist (pig manure) that generates in the pig farm, it locates in the city of Latacunga, in Salache. The pig farm has a total of 15 pigs that generate a daily manure production of 23.5 kg per day of excreta and biogas production of biogas 1.198 m^3 per day, therefore, the aim is to design a small plant that will allow treatment of hog manure generated in The Salache Campus and in the same way to obtain electric power, in order to reduce energy costs. This project was carried out in order to assess the resource and sizing a system of generation to provide part of the electrical power in the UTC`s poultry, in such a way that based on the calculations obtained a total of 2.635 kwh per day. Besides, conducted a design guide for the production of biogas through a tubular biodigester system where also determines the necessary calculations to establish the size of the ditch and elements necessary to operate the biodigester. We analyzed the installed load for the estimation of demand for poultry and granted will need a generator of power 800 W for providing part of the electrical energy of the poultry.